CircRNA Chordc1 protects mice from abdominal aortic aneurysm by contributing to the phenotype and growth of vascular smooth muscle cells - Xiang He; Xinzhong Li; Yuan Han; Guojun Chen; Tong Xu; Donghua Cai; Yili Sun; Shifei Wang; Yanxian Lai; Zhonghua Teng; Senlin Huang; Wangjun Liao; et al. (Elsevier, 2022)
Circular RNAs (circRNAs) have important potential in modulating vascular smooth muscle cell (VSMC) activity, but their roles in abdominal aortic aneurysm (AAA) are unknown. We performed in situ hybridization and immunohistochemistry and determined that circChordc1 (cysteine and histidine-rich domain containing 1) was markedly downregulated in aneurysm tissue compared with normal arteries. A gene gain and loss strategy was used to confirm that circChordc1 transformed VSMCs into a contracted phenotype and improved their growth, which significantly suppressed aneurysm formation and reduced the risk of rupture in mouse models of angiotensin (Ang) II- and CaCl2-induced AAA. RNA pull-down, immunoprecipitation, and immunoblotting indicated that circChordc1 facilitated the VSMC phenotype and growth determination by binding to vimentin and ANXA2 (annexin A2), which not only increased vimentin phosphorylation to promote its degradation but also promoted the interaction between ANXA2 and glycogen synthase kinase 3 beta (GSK3β) to induce the nuclear entry of β-catenin. Thus, our present study revealed that circChordc1 optimized the VSMC phenotype and improved their growth by inducing vimentin degradation and increasing the activity of the GSK3β/β-catenin pathway, thereby extenuating vascular wall remodeling and reversing pathological aneurysm progression.